Crosslinked netted water-soluble polymer paper reinforcing agent and preparation method thereof

By cross-linking polyvinyl alcohol and sodium carboxymethylcellulose under mild conditions and supplemented with silicone modification, the problem of harsh conditions for cross-linking of PVA and CMC is solved, and the paper strength and moisture resistance are improved, and production costs and environmental risks are reduced.

CN119529331AActive Publication Date: 2025-02-28SHAANXI UNIV OF SCI & TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411728708.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-28
Estimated Expiration
2044-11-28

AI Technical Summary

Technical Problem

In the prior art, PVA and CMC crosslinking require strict reaction conditions, and it is impossible to balance good crosslinking effects and material properties.

Method used

By crosslinking polyvinyl alcohol with sodium carboxymethylcellulose system at 60-120°C and modifying with silicone, a crosslinked network structure was designed to form a paper reinforcement with better performance.

Benefits of technology

Cross-linking under relatively mild conditions is achieved, the paper strength and moisture resistance are improved, and it has good compatibility, fluidity and adhesion, reducing production costs and environmental risks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119529331A_ABST
    Figure CN119529331A_ABST
Patent Text Reader

Abstract

The invention discloses a cross-linked netted water-soluble polymer paper reinforcing agent and a preparation method thereof, and belongs to the field of paper reinforcing, at 60-120 DEG C, a catalyst and an amino-containing cross-linking agent are added into a mixed solution dissolved with polyvinyl alcohol and sodium carboxymethyl cellulose while stirring, the catalyst is zinc chloride or aluminum chloride, and then heat preservation treatment is performed; and cooling the obtained reaction system, adding a silane coupling agent, then preserving heat for 0.5-2 hours, and adjusting the pH value of the obtained reaction system to be neutral to obtain the cross-linked network water-soluble polymer paper reinforcing agent, which has wide application prospects in the production of various types of paper (such as packaging paper, writing paper, printing paper and the like).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of paper reinforcement, and in particular relates to a cross-linked network water-soluble polymer paper reinforcement agent and a preparation method thereof. Background Art

[0002] Paper enhancement refers to improving the physical properties and durability of paper through various methods and technologies. Generally, high-strength, high-quality fiber raw materials, such as chemical wood pulp fibers, are selected to improve the basic strength of paper, or special fibers or artificial polymers are introduced to further improve the strength and durability of paper. The use of paper enhancers (such as amphiphilic multi-molecular polymers) can effectively improve the stiffness, tear length, folding resistance and other properties of paper. Paper enhancers enhance the bonding force between fibers by forming hydrogen bonds and cross-linking bonds.

[0003] At present, the commonly used paper strengthening agents are modified starch, polyacrylamide and its derivatives, urea-formaldehyde resin and its modified products. Among them, modified starch is one of the most widely used paper strengthening agents, but it has a low water filtration rate and cannot meet the high dry strength and folding resistance. When polyacrylamide and its derivatives are used as dry strength agents, the tear strength improvement effect is not obvious or even reduced. Urea-formaldehyde resin and its modified products have uneven interaction with fibers, and the dilution and local concentration are difficult to control. There is also the environmental problem of formaldehyde release.

[0004] CMC has good water solubility, thickening, water retention and adhesion, can improve the dry strength and wet strength of paper, improve the uniformity of paper, and can be used in combination with other dry and wet strength agents to further improve paper performance. PVA has good film-forming and adhesion properties, can form a protective film on the surface of paper, improve paper strength and water resistance, and after cross-linking with CMC, it can form a more stable three-dimensional network structure, significantly improve the mechanical properties of paper, reduce the hydrophilicity of CMC and PVA, reduce the effect of water on paper strength, and can also adjust the viscosity and fluidity of the system, so that the coating of the reinforcing agent is more uniform, and improve the surface quality and printing adaptability of paper. Therefore, in theory, CMC and PVA can be prepared into paper reinforcing agents, but there are some problems when cross-linking PVA and CMC: first, harsh reaction conditions are required, such as high temperature, high pressure or special catalysts, which not only increases production costs, but also has high requirements for equipment; second, it is impossible to simultaneously take into account the good cross-linking effect and the balance of material properties. Summary of the invention

[0005] In view of the problems existing in the prior art, the present invention provides a cross-linked network water-soluble polymer paper reinforcing agent and a preparation method thereof, so as to solve the problems that harsh reaction conditions are required when PVA and CMC are cross-linked and a good cross-linking effect and a balance between material performance cannot be taken into account at the same time. Based on a polymer polymerization reaction, polyvinyl alcohol and a sodium carboxymethyl cellulose system are cross-linked to form a cross-linked network structure, and organic silicon modification is used to increase the solid content of the reinforcing agent, enhance the bonding force, and prepare a paper reinforcing agent with better performance.

[0006] The present invention is achieved through the following technical solutions: A method for preparing a cross-linked network water-soluble polymer paper strengthening agent comprises the following steps: S1, adding a catalyst and an amino-containing crosslinking agent to a mixed solution containing polyvinyl alcohol and sodium carboxymethyl cellulose while stirring at 60-120°C, wherein the catalyst is zinc chloride or aluminum chloride, and the mass ratio of polyvinyl alcohol to sodium carboxymethyl cellulose is (1-5):(1-3), followed by heat preservation treatment, wherein the amino group of the crosslinking agent reacts with the hydroxyl group of the polyvinyl alcohol and the carboxyl group of the sodium carboxymethyl cellulose to gradually form an intermediate product with a crosslinking structure, thereby obtaining a reaction system a; S2, cooling the reaction system a, adding a silane coupling agent, and then keeping the temperature for 0.5-2 hours to obtain a reaction system b, adjusting the pH of the reaction system b to neutral, and obtaining a cross-linked network water-soluble polymer paper strengthening agent.

[0007] Preferably, S1 obtains the mixed solution by the following process: Dissolve polyvinyl alcohol and sodium carboxymethyl cellulose in deionized water at 60-120° C. and 50-80° C., respectively, to obtain a polyvinyl alcohol solution with a mass percentage of 5%-20% and a sodium carboxymethyl cellulose solution with a mass percentage of 2%-10%; The polyvinyl alcohol solution and the sodium carboxymethyl cellulose solution are mixed and stirred at 50-60° C. for 30-60 minutes at a stirring speed of 300-500 r / min to obtain the mixed solution.

[0008] Preferably, the cross-linking agent described in S1 is urea.

[0009] Preferably, the urea is 3%-15% of the total mass of polyvinyl alcohol and sodium carboxymethyl cellulose, and the catalyst is 3% of the mass of urea.

[0010] Preferably, S1 adds the mixed aqueous solution of the crosslinking agent and the catalyst dropwise while stirring, and the dropping time is controlled within 30-150 min.

[0011] Preferably, the heat preservation treatment described in S1 is carried out at 60-120° C. for 0.5-2 h.

[0012] Preferably, S2 cools the reaction system a to 65-75° C., and then adds a silane coupling agent.

[0013] Preferably, the silane coupling agent is (3-glycidyl propoxy) trimethoxy silane, and the content of (3-glycidyl propoxy) trimethoxy silane is 1%-10% of the total mass of polyvinyl alcohol and sodium carboxymethyl cellulose.

[0014] Preferably, S2 is added with (3-glycidylpropoxy)trimethoxysilane in a dropwise manner, and the dropwise addition time is controlled within 30-120 min.

[0015] A cross-linked network water-soluble polymer paper reinforcing agent obtained by any one of the above-mentioned preparation methods of the cross-linked network water-soluble polymer paper reinforcing agent.

[0016] Compared with the prior art, the present invention has the following beneficial technical effects: The invention discloses a method for preparing a cross-linked network water-soluble polymer paper reinforcing agent. Under the catalytic action of zinc chloride or aluminum chloride, the amino group of the cross-linking agent reacts with the hydroxyl group of PVA and the carboxyl group of CMC through temperature conditions to gradually form an intermediate product with a cross-linked structure. Then, cooling can promote a silane coupling agent to undergo a condensation reaction with the terminal hydroxyl group of the intermediate product to achieve end-capping, thereby obtaining a cross-linked network water-soluble polymer paper reinforcing agent. The cross-linking system can be realized under relatively mild conditions, does not require extreme temperature and pressure reaction conditions, and can improve the strength and moisture resistance of paper. The reinforcing agent has good compatibility, good fluidity, uniform film formation, strong adhesion, good compatibility with various synthetic latexes, good mildew resistance, stable performance, fast drying speed, convenient use, and low cost. Zinc chloride or aluminum chloride is common, relatively low in cost, and widely available, which helps to reduce the overall production cost. Zinc chloride or aluminum chloride has relatively low toxicity, and compared with some heavy metal catalysts or highly corrosive catalysts, it is less harmful to operators and the environment during the production process, which makes the invention more advantageous in terms of environmental protection and safety. Compared with some cross-linking processes that require high temperature and high pressure, the present invention can achieve good cross-linking effects at lower temperatures and normal pressures, thereby reducing dependence on special equipment and further reducing production costs. The raw materials used in the present invention are non-toxic and pollution-free, and are more suitable for industrial production. When used together with other additives in the papermaking process (such as sizing agents and fillers), no adverse reactions will occur, and no adverse effects will be produced on other important properties of the paper, such as whiteness and printability. The paper enhancer of the present invention has broad application prospects in the production of various types of paper (such as packaging paper, writing paper, printing paper, etc.), and can meet the needs of the paper industry for improving paper strength performance, while better maintaining the water solubility of the material, so that it has application potential in more fields.

[0017] Furthermore, the present invention adopts urea as a cross-linking agent, and the amino groups in the urea molecules are more likely to react effectively with the hydroxyl groups on the PVA molecular chain and the carboxyl groups on the CMC molecular chain. Under the catalytic action of zinc chloride or aluminum chloride, the reaction can proceed more quickly and fully, and the reaction conditions are milder. No complicated equipment and special catalysts are required, which greatly reduces the production cost, thereby forming a cross-linked network structure between molecules and enhancing the mechanical properties, integrity and stability of the system.

[0018] Furthermore, the present invention uses KH560 end-capping. The (3-glycidyl propoxy) trimethoxysilane part in the molecular structure of KH560 has unique chemical activity and can react specifically with the active sites after PVA / CMC cross-linking to achieve efficient end-capping. This high efficiency can more accurately control the surface properties of the material, such as improving hydrophobicity, improving compatibility with starch materials or polyacrylamide materials and interaction with paper fibers, so that it can play a better role in some application scenarios that require moisture and water resistance. Compared with traditional end-capping technology, KH560 end-capping brings more functions to the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is the infrared spectrum of G3-PVA / CMC obtained in Example 3 of the present invention.

[0020] Figure 2 This is the thermal stability analysis curve of G3-PVA / CMC obtained in Example 3 of the present invention.

[0021] Figure 3 The figure is the effect of the urea dosage on the dry tensile strength and wet tensile strength of paper according to the present invention.

[0022] Figure 4 The figure is the influence of the urea dosage on the folding endurance and tearing strength of paper according to the present invention.

[0023] Figure 5 The figure is the influence of the urea dosage on the ring crush index and surface water absorption of paper of the present invention. DETAILED DESCRIPTION

[0024] The above contents of the present invention are further described in detail below through examples, but this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples, and all technologies implemented based on the above contents of the present invention belong to the scope of the present invention.

[0025] The invention discloses a cross-linked network water-soluble polymer paper strengthening agent. The raw materials include component I, component II, component III, a silane coupling agent and a catalyst. The mass ratio of component I (polyvinyl alcohol) to component II (sodium carboxymethyl cellulose) is (1-5):(1-3), the mass of component III (urea, cross-linking) is 3-15% of the total mass of components I and II, the mass of the silane coupling agent ((3-glycidyl propoxy) trimethoxy silane)) is 1-10% of the total mass of components I and II, and the catalyst (zinc chloride or aluminum chloride) is 3% of the mass of urea.

[0026] The present invention provides a method for preparing a cross-linked network water-soluble polymer paper strengthening agent, comprising the following steps: Dissolve PVA (polyvinyl alcohol) and CMC-Na (sodium carboxymethyl cellulose, written as CMC for the sake of simplicity) in deionized water, respectively, the dissolution temperature of PVA is 60-120°C, and the dissolution temperature of CMC is 50-80°C. Then mix the PVA solution (5-20% by mass) and the CMC solution (light yellow transparent solution) with a mass percentage of 2-10%, stir at 50-60°C for 30-60 minutes, and the stirring speed is 300-500r / min to obtain a uniform PVA / CMC mixed solution.

[0027] The degree of polymerization of polyvinyl alcohol is between 300-3000, the degree of alcoholysis is between 88%-98%, and the mass concentration of its aqueous solution is between 5%-20%.

[0028] After heating the PVA / CMC mixed solution to 60-120°C, slowly drip a mixed aqueous solution of urea and zinc chloride or aluminum chloride (dissolved at room temperature, the mass ratio of urea to water is 1:30) while stirring, the stirring speed is 300r / min, zinc chloride or aluminum chloride is used as a catalyst, the dripping time is controlled at 30-150min, and the temperature is kept for 0.5-2 hours after the dripping is completed. In this process, the amino group of urea reacts with the hydroxyl group of PVA and the carboxyl group of CMC to gradually form a cross-linked structure. After the reaction is completed, a cross-linked intermediate product is obtained.

[0029] The cross-linked product is cooled to 65-75°C, and KH560 (3-glycidylpropoxy)trimethoxysilane) is slowly added dropwise. The addition time is controlled at 30-120 min. After the addition is completed, the mixture is kept warm for 0.5-2 hours. The stirring speed is 200-400 r / min. The silanol produced by the hydrolysis of KH560 undergoes a condensation reaction with the terminal hydroxyl group of the cross-linked intermediate product to achieve end-capping. Subsequently, the pH is adjusted to neutral with 26% ammonia water by volume to obtain a cross-linked network water-soluble polymer paper enhancer in the form of an emulsion.

[0030] The reaction equation for crosslinking CMC (carboxymethyl cellulose) and PVA (polyvinyl alcohol) with urea (catalyzed by zinc chloride) is as follows: For the reaction of CMC's carboxyl group (-COOH) with urea (H2N-CONH2): Under the catalysis of zinc chloride or aluminum chloride, the reaction formula is -COOH+H2N-CONH2→CO-NH-CONH2+H2O.

[0031] Reaction of hydroxyl group (-OH) of PVA with urea: -OH+H2N-CONH2→-O-CO-NH-NH2+H2O The KH560 (γ-(2,3-epoxypropoxy)propyltrimethoxysilane) end-capping reaction equation is as follows: The terminal hydroxyl group (-OH) of CMC or PVA reacts with the epoxy group (CH2-CH-CH2O) of KH560: -OH+CH2-CH-CH2O→HO-CH2-CH(OH)-CH2-O-polymer chain Example 1 Select PVA with a degree of polymerization of 1799 and a degree of alcoholysis of 98%. Slowly add PVA to deionized water and stir at 90°C for 2 hours until it is completely dissolved to obtain a PVA solution with a mass percentage of 10%. Select CMC with a degree of substitution of 0.7. Slowly add CMC to deionized water at room temperature and stir at 60°C for 3 hours to obtain a CMC solution with a mass percentage of 5%.

[0032] The PVA solution and the CMC solution were mixed at a solid content mass ratio of 5:2, stirred at 60° C. for 20 min at a stirring speed of 200 r / min to obtain a uniform PVA / CMC mixed solution.

[0033] After the PVA / CMC mixed solution was heated to 80°C, a mixed aqueous solution of urea and zinc chloride was added dropwise, the amount of urea added was 5% of the total mass of PVA and CMC, and zinc chloride was added as a catalyst, the amount of zinc chloride added was 3% of the mass of urea, the dropping time was controlled at 60min, and the temperature was kept for 2h after the dropping was completed. Stirring was continued during the reaction at a speed of 300r / min. Under the catalysis of zinc chloride, the amino groups in the urea molecules reacted with the hydroxyl groups on the PVA and CMC molecular chains to cross-link. After the reaction was completed, the temperature was lowered to 70°C, and KH560 was slowly added dropwise to the reaction system. The amount of KH560 added was 3% of the total mass of PVA and CMC, the dropping time was controlled at 30min, and after the dropping was completed, it was stirred at 70°C for 2h at a stirring speed of 200r / min. The silanol produced by the hydrolysis of KH560 reacted with the hydroxyl groups of the cross-linking intermediates to achieve end-capping. The pH was adjusted to neutral using 26% ammonia water by volume to obtain a cross-linked network water-soluble polymer paper reinforcing agent, namely sample G1-PVA / CMC.

[0034] Example 2 Select PVA with a degree of polymerization of 1799 and a degree of alcoholysis of 98%. Slowly add PVA to deionized water and stir at 90°C for 2 hours until it is completely dissolved to obtain a PVA solution with a mass percentage of 10%. Select CMC with a degree of substitution of 0.7. Slowly add CMC to deionized water at room temperature and stir at 60°C for 3 hours to obtain a CMC solution with a mass percentage of 5%.

[0035] The PVA solution and the CMC solution were mixed at a solid content mass ratio of 5:2, stirred at 60° C. for 30 min at a stirring speed of 200 r / min to obtain a uniform PVA / CMC mixed solution.

[0036] After the PVA / CMC mixed solution was heated to 80°C, a mixed aqueous solution of urea and zinc chloride was added dropwise, the amount of urea added was 8% of the total mass of PVA and CMC, and zinc chloride was added as a catalyst, the amount of zinc chloride added was 3% of the mass of urea, the dropping time was controlled at 60min, and the temperature was kept for 2h after the dropping was completed. Stirring was continued during the reaction at a speed of 300r / min. Under the catalysis of zinc chloride, the amino groups in the urea molecules reacted with the hydroxyl groups on the PVA and CMC molecular chains to cross-link. After the reaction was completed, the temperature was lowered to 70°C, and KH560 was slowly added dropwise to the reaction system. The amount of KH560 added was 3% of the total mass of PVA and CMC, the dropping time was controlled at 30min, and after the dropping was completed, it was stirred at 70°C for 2h at a stirring speed of 200r / min. The silanol produced by the hydrolysis of KH560 reacted with the hydroxyl groups of the cross-linking intermediates to achieve end-capping. The pH was adjusted to neutral using 26% ammonia water by volume to obtain a cross-linked network water-soluble polymer paper reinforcing agent, namely sample G2-PVA / CMC.

[0037] Example 3 Select PVA with a degree of polymerization of 1799 and a degree of alcoholysis of 98%. Slowly add PVA to deionized water and stir at 90°C for 2 hours until it is completely dissolved to obtain a PVA solution with a mass percentage of 10%. Select CMC with a degree of substitution of 0.7. Slowly add CMC to deionized water at room temperature and stir at 60°C for 3 hours to obtain a CMC solution with a mass percentage of 5%.

[0038] The PVA solution and the CMC solution were mixed at a solid content mass ratio of 5:2, stirred at 70° C. for 30 min at a stirring speed of 200 r / min to obtain a uniform PVA / CMC mixed solution.

[0039] After the PVA / CMC mixed solution is heated to 80°C, a mixed aqueous solution of urea and zinc chloride is added dropwise. The amount of urea added is 10% of the total mass of PVA and CMC. Zinc chloride is added as a catalyst at the same time. The amount of zinc chloride added is 3% of the mass of urea. The dropping time is controlled at 60min. After the dropping is completed, it is kept warm for 2h. Stirring is continued during the reaction at a stirring speed of 300r / min. Under the catalysis of zinc chloride, the amino groups in the urea molecules react with the hydroxyl groups on the PVA and CMC molecular chains to cross-link. After the reaction is completed, the temperature is lowered to 70°C, and KH560 is slowly added dropwise to the reaction system. The amount of KH560 added is 3% of the total mass of PVA and CMC. The dropping time is controlled at 30min. After the dropping is completed, it is stirred at 70°C for 2h at a stirring speed of 200r / min. The silanol produced by the hydrolysis of KH560 reacts with the hydroxyl groups of the cross-linking intermediates to achieve end-capping. The pH was adjusted to neutral using 26% ammonia water by volume to obtain a cross-linked network water-soluble polymer paper reinforcing agent, namely sample G3-PVA / CMC.

[0040] Example 4 Select PVA with a degree of polymerization of 1799 and a degree of alcoholysis of 98%. Slowly add PVA to deionized water and stir at 90°C for 2 hours until it is completely dissolved to obtain a PVA solution with a mass percentage of 10%. Select CMC with a degree of substitution of 0.7. Slowly add CMC to deionized water at room temperature and stir at 60°C for 3 hours to obtain a CMC solution with a mass percentage of 5%.

[0041] The PVA solution and the CMC solution were mixed at a solid content mass ratio of 5:2, stirred at 70° C. for 30 min at a stirring speed of 200 r / min to obtain a uniform PVA / CMC mixed solution.

[0042] After the PVA / CMC mixed solution is heated to 80°C, a mixed aqueous solution of urea and zinc chloride is added dropwise. The amount of urea added is 15% of the total mass of PVA and CMC. Zinc chloride is added as a catalyst at the same time. The amount of zinc chloride added is 3% of the mass of urea. The dropping time is controlled at 60min. After the dropping is completed, it is kept warm for 2h. Stirring is continued during the reaction at a stirring speed of 300r / min. Under the catalysis of zinc chloride, the amino groups in the urea molecules react with the hydroxyl groups on the PVA and CMC molecular chains to cross-link. After the reaction is completed, the temperature is lowered to 70°C, and KH560 is slowly added dropwise to the reaction system. The amount of KH560 added is 3% of the total mass of PVA and CMC. The dropping time is controlled at 30min. After the dropping is completed, it is stirred at 70°C for 2h at a stirring speed of 200r / min. The silanol produced by the hydrolysis of KH560 reacts with the hydroxyl groups of the cross-linking intermediates to achieve end-capping. The pH was adjusted to neutral using 26% ammonia water by volume to obtain a cross-linked network water-soluble polymer paper reinforcing agent, namely sample G4-PVA / CMC.

[0043] Structure and performance testing FT-IR analysis of cross-linked network water-soluble polymer paper strengthening agent (G-PVA / CMC) Figure 1 This is the infrared spectrum of G-PVA / CMC. -1 The wide strong absorption peak is the hydroxyl (-OH) stretching vibration absorption peak. Due to the presence of water, this absorption peak is wide and strong; at 2937cm -1 The stretching vibration absorption peak of the saturated CH bond appears, which is the characteristic peak of alkyl compounds and is consistent with the carbon chain structure in KH560; at 2063cm -1 The characteristic absorption peak of -C≡N- is at 1635cm -1 The strong C=O stretching vibration absorption peak appears at the , proving the existence of a cross-linked structure between PVA and CMC, which is consistent with the structural characteristics of G-PVA / CMC.

[0044] Thermogravimetric analysis of cross-linked network water-soluble polymer paper strengthening agent (G-PVA / CMC) The heating mass loss and integral curve of the emulsion after drying were tested and analyzed to explore the effect of temperature on the stability of the polymer. The results are as follows: Figure 2 As shown. Figure 2It can be seen that with the increase of temperature, the mass loss of the enhancer presents three different stages and finally reaches a state of equilibrium; the mass loss rate shows a trend of first slow, then accelerated, and then gradually stabilized. In the first stage when the temperature does not exceed 200 °C, the mass of the enhancer changes by 7.88%, which is the evaporation of water; in the stage of 200-300 °C, a small amount of side chain groups on the molecular chain are pyrolyzed; in the third stage, when the temperature does not exceed 300-400 °C, the mass loss rate is significantly accelerated, and the mass change is as high as 44.25%, which is mainly manifested by the breakage of the main chain segment of the paper enhancer.

[0045] The cross-linked network water-soluble polymer paper reinforcing agent prepared as above was used for surface sizing of corrugated base paper waste paper: the base paper was cut into a size of 15 cm × 30 cm, impregnated with an appropriate amount of G-PVA / CMC sizing agent for 3 minutes, placed on a roller coater, and the sizing agent was evenly coated on the paper using a sizing roller, so that the cross-linked network water-soluble polymer paper reinforcing agent was adsorbed on the fiber through hydrogen bonding and electrostatic action, and finally it was vacuum dried at 105°C for 10 minutes, and the physical properties of the finished paper were tested.

[0046] The physical properties of paper are tested and calculated in accordance with national standards. The tensile index refers to GB / T 12914-2008 Determination of tensile strength of paper and paperboard; the tear index refers to GB / T 455-2002 Determination of tear resistance of paper and paperboard; the folding endurance refers to GB / T 457-2008 Determination of folding endurance of paper and paperboard; the ring crush index refers to GB / T 2679.8-2016 Determination of ring crush strength of paper and paperboard; the water absorption test (60 scobb value) refers to GB / T 1540-2002 Determination of water absorption of paper and paperboard.

[0047] Effect of urea dosage on paper strength properties In order to determine the optimal content of urea, the effect of the addition amount of cross-linked network water-soluble polymer paper strengthening agent urea on the strength properties of paper was studied. The results are as follows Figure 3 , Figure 4 and Figure 5 As shown in the figure, with the increase of urea content, the dry and wet tensile index of the sized paper both show an upward trend. This is because the cross-linked network water-soluble polymer paper enhancer itself has an electrostatic attraction with the paper fiber and is adsorbed on the fiber surface. In addition, the hydroxyl functional groups on the polymer chain segments will also form hydrogen bonds with the hydroxyl groups on the fiber, thereby increasing the toughness and strength between the fibers. When the urea content is 8.0%, the dry tensile index of the paper is 78.3Nm / g, the wet tensile index is 4.63Nm / g, the folding endurance is 11 times, and the tear index is 6.6Nm 2 / g, ring pressure index 4.7Nmg -1 , surface water absorption rate 84.3g / m2 Compared with the paper without internal sizing, the strength indexes of the paper increased by 318.7%, 69.8%, 100%, 522.6%, 50.4% and 18.9% respectively. However, with the continuous increase of urea content, the dry and wet strength indexes of the paper decreased. This is because too much urea will compete with PVA and CMC for reaction sites, interfere with the normal cross-linking process, and lead to incomplete or unstable cross-linking structure, thus reducing the strength of the paper.

Claims

1. A method for preparing a cross-linked network water-soluble polymer paper strengthening agent, characterized in that: The steps include: S1, adding a catalyst and an amino-containing crosslinking agent to a mixed solution containing polyvinyl alcohol and sodium carboxymethyl cellulose while stirring at 60-120° C., wherein the catalyst is zinc chloride or aluminum chloride, and the mass ratio of polyvinyl alcohol to sodium carboxymethyl cellulose is (1-5):(1-3), followed by heat preservation treatment to obtain a reaction system a; S2, cooling the reaction system a, adding a silane coupling agent, and then keeping the temperature for 0.5-2 hours to obtain a reaction system b, adjusting the pH of the reaction system b to neutral, and obtaining a cross-linked network water-soluble polymer paper strengthening agent.

2. The method for preparing the cross-linked network water-soluble polymer paper strengthening agent according to claim 1, characterized in that: S1 obtains the mixed solution by the following process: Dissolve polyvinyl alcohol and sodium carboxymethyl cellulose in deionized water at 60-120° C. and 50-80° C., respectively, to obtain a polyvinyl alcohol solution with a mass percentage of 5%-20% and a sodium carboxymethyl cellulose solution with a mass percentage of 2%-10%; The polyvinyl alcohol solution and the sodium carboxymethyl cellulose solution are mixed and stirred at 50-60° C. for 30-60 minutes at a stirring speed of 300-500 r / min to obtain the mixed solution.

3. The method for preparing the cross-linked network water-soluble polymer paper strengthening agent according to claim 1, characterized in that: The cross-linking agent described in S1 is urea.

4. The method for preparing the cross-linked network water-soluble polymer paper strengthening agent according to claim 3, characterized in that: The urea is 3%-15% of the total mass of polyvinyl alcohol and sodium carboxymethyl cellulose, and the catalyst is 3% of the mass of urea.

5. The method for preparing the cross-linked network water-soluble polymer paper strengthening agent according to claim 1, characterized in that: S1: adding the mixed aqueous solution of the crosslinking agent and the catalyst dropwise while stirring, and the dropping time is controlled within 30-150 minutes.

6. The method for preparing the cross-linked network water-soluble polymer paper strengthening agent according to claim 1, characterized in that: The heat preservation treatment described in S1 is carried out at 60-120° C. for 0.5-2 h.

7. The method for preparing the cross-linked network water-soluble polymer paper strengthening agent according to claim 1, characterized in that: S2 cools the reaction system a to 65-75°C and then adds a silane coupling agent.

8. The method for preparing the cross-linked network water-soluble polymer paper strengthening agent according to claim 1, characterized in that: The silane coupling agent is (3-glycidyl propoxy) trimethoxy silane, and the (3-glycidyl propoxy) trimethoxy silane is 1%-10% of the total mass of polyvinyl alcohol and sodium carboxymethyl cellulose.

9. The method for preparing the cross-linked network water-soluble polymer paper strengthening agent according to claim 1, characterized in that: S2 is added with (3-glycidylpropoxy)trimethoxysilane in a dropwise manner, and the dropping time is controlled within 30-120 min.

10. A cross-linked network water-soluble polymer paper strengthening agent obtained by the preparation method of the cross-linked network water-soluble polymer paper strengthening agent according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Surface glue reinforcing agent and preparation method thereof

    CN106283867A

  • Preparation method and application of sodium carboxymethylcellulose-diketene grafted copolymer

    CN108892751A

  • Paper processing chemical

    JP2008280653A